An updated meta-analysis of the association between Toxoplasma gondii infection and risk of epilepsy. (21st May 2019) - Sadeghi, Maryam; Riahi, Seyed Mohammad; Mohammadi, Mona; Saber, Vafa; Aghamolaie, Somayeh; Moghaddam, Solmaz Alizadeh; Aghaei, Shima; Javanian, Mostafa; Gamble, H Ray; Rostami, Ali
Abstract: Toxoplasma gondii is a neurotropic pathogen with worldwide distribution. To evaluate the association between Toxoplasma infection and the risk of epilepsy by meta-analysis, observational peer-reviewed studies were retrieved from PubMed, Embase, Web of Science, Scopus and Google Scholar (up to 10 October 2018) and by reference review. Pooled risk estimates were calculated using a random effects model. Heterogeneity was assessed using Cochrane's Q-test and I 2 . In total, 16 eligible studies involving 19 data sets were included for the final analysis. A total 7897 participants (3771 epileptic patients, 4026 healthy controls) were included. The pooled odds ratio (OR) for Toxoplasma infection was increased to 1.72 (95% confidence interval [CI] 1.37 to 2.16) among patients with epilepsy. There was moderate heterogeneity among the studies (χ 2 =39.8, I 2 =62.3%, p=0.001). The ORs from subgroup analyses showed that both cryptogenic epilepsy (OR 2.65 [95% CI 1.91 to 3.68]) and active convulsive epilepsy (OR 1.37 [95% CI 1.09 to 1.72]) were significantly associated with Toxoplasma infection. Another subgroup analyses according to age showed a significant positive association in children (OR 1.33), adults (OR 1.57) and in all ages (OR 1.89). Our findings support the association between Toxoplasma infection and epilepsy. More prospective studies with larger sample sizes and more experimental studies are recommended to elucidate a causative relationship.